Relationship Between Structural Official’s Characteristics And Staff Attendance Discipline At L Hospital - Rochmi Nurbaiti; Pipit Festi Wiliyanarti (Global Journal of Health Administration, 2026)
Abstract Background : In hospital administration, attendance discipline is a crucial operational metric. In their work units, structural officials are directly in charge of overseeing and promoting employee discipline. The relationship between structural officials' formal characteristics (educational level, years in current position, and managerial training certification) and actual staff attendance discipline is still poorly understood, especially in Indonesian hospital settings, despite the fact that leadership behaviours have been thoroughly studied Aims : Analyze the relationship between the formal attributes of structural officials (educational level, years in current position, and managerial certification) and the number of staff attendance violations (lateness >100 minutes) at Hospital L between June and December 2025 Methods : A cross-sectional quantitative analysis utilising secondary data from L  Hospital personnel and attendance records. All 39 structural officials who are currently in office were included in the total sampling. Spearman correlation, the Mann-Whitney U test (X3), and multiple linear regression with log(Y+1) transformation were used to analyse the data in order to address the dependent variable's non-normality. Results : No significant relationships were found between educational level (rs = −0.18, p = 0.280), years in current position (rs = +0.22, p = 0.184), or managerial certification (U = 104.0, p = 0.118) and staff lateness counts. The simultaneous model explained only 14.0% of total variance (R² = 0.140; F = 1.896; p = 0.148). Conclusion : Staff attendance discipline is not strongly predicted by the formal traits of structural officials. Active behavioural leadership techniques, organisational culture, and contextual elements like unit workload and supervisory intensity are more likely to influence staff discipline. It is advised that hospitals incorporate competency-focused managerial training programmes and behavior-based leadership assessments into their structural appointment procedures Keywords : attendance discipline; hospital management; leadership characteristics; managerial certification; structural official Abstrak Latar Belakang : Kepuasan pasien merupakan salah satu indikator penting dalam menilai kualitas pelayanan rumah sakit. Kualitas pelayanan yang mencakup dimensi tangible, reliability, responsiveness, assurance, dan empathy dapat memengaruhi tingkat kepuasan pasien terhadap pelayanan kesehatan yang diberikan. Tujuan : Penelitian ini bertujuan untuk menganalisis kepuasan pasien terhadap pelayanan di Rumah Sakit Al-Irsyad Surabaya Tahun 2025. Metode : Desain penelitian yang digunakan adalah cross sectional dengan jumlah populasi sebanyak 4.875 pasien dan sampel penelitian sebanyak 110 responden yang dipilih menggunakan teknik purposive sampling. Penelitian dilaksanakan pada bulan Juli 20252. Pengumpulan data dilakukan menggunakan kuesioner berdasarkan dimensi kualitas pelayanan (tangible, reliability, responsiveness, assurance, dan empathy). Analisis data dilakukan menggunakan uji Chi-Square dan uji regresi logistik multivariat. Hasil : Hasil analisis statistik menggunakan uji Chi-Square menunjukkan adanya hubungan yang bermakna antara variabel reliability (p=0,021), assurance (p=0,015), dan empathy (p=0,008) dengan kepuasan pasien (p<0,05). Sementara itu, variabel tangible dan responsiveness tidak menunjukkan hubungan yang signifikan. Hasil uji regresi logistik multivariat menunjukkan bahwa faktor yang paling dominan memengaruhi kepuasan pasien adalah empathy (p=0,003; OR=9,472). Kesimpulan : Pihak rumah sakit perlu meningkatkan mutu pelayanan melalui penguatan komunikasi interpersonal, peningkatan perhatian individual kepada pasien, serta peningkatan kompetensi dan sikap profesional tenaga kesehatan dalam memberikan pelayanan yang berorientasi pada kebutuhan pasien. Kata Kunci : Kepuasan pasien, kualitas pelayanan, SERVQUAL, rumah sakit.